Preventing Abuse and Neglect in the Lives of Children with Disabilities - Crowley, E. Paula; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book addresses the development of our understanding of abuse and neglect in the lives of children with disabilities. Disabilities in childhood uniquely dispose children for their abuse and neglect. Additionally, abuse and neglect dispose children for disabilities. The care and education of children with disabilities requires unique knowledge and skills and so does the consideration of their abuse and neglect. This book is based on data generated from an analysis of cases involving the abuse and neglect of children with disabilities as well as on an analysis of the data based literature in this area. Readers are provided with analysis and reflection exercises throughout the text so that they may analyze and reflect on their own awareness of the abuse and neglect of children with disabilities. Each chapter also contains a set of implications for research and practice. The final chapter focuses directly on prevention. Caregivers and professionals across disciplines will develop a new understanding of their roles in universal, secondary, and tertiary level prevention that is targeted, focused, data-based, and designed to prevent the abuse and neglect of children with disabilities in the first place.
Part I: What Do We Know about Abuse and Neglect and Child Disability? -- Chapter 1. The Abuse and Neglect of Children with Disabilities: The Extent of the Problem -- Chapter 2. Age, Sex, Disability and Other Characteristics of Children with Disabilities Who Are Abused and Neglected -- Chapter 3. The Forms of Abuse and Neglect of Children with Disabilities -- Chapter 4. The Outcomes of the Abuse and Neglect of Children with Disabilities -- Part II. What Do We Know about the Perpetrators of Abuse and Neglect of Children with Disabilities -- Chapter 5. The Age and Sex of the Perpetrators of Abuse and Neglect in the Lives of Children with Disabilities -- Chapter 6. The Roles and Relationships of the Perpetrators to the Children with Disabilities They Abuse and Neglect -- Chapter 7. The Disabilities of the Perpetrators in the Lives of Children with Disabilities -- Part III. How Can We Predict and Prevent the Deadly Abuse and Neglect of Children with Disabilities -- Chapter 8. Understanding the Context of Abuse and Neglect of Children with Disabilities -- Chapter 9. Our Professional Failures at Predicting and Preventing Abuse and Neglect in the Lives of Children with Disabilities -- Chapter 10. Preventing Abuse and Neglect in the Lives of Children with Disabilities. .
Keywords: Maternal and infant welfare; Early childhood education; Developmental psychology